2009
DOI: 10.1177/1352458508095920
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of 25-hydroxyvitamin D are associated with a lower incidence of multiple sclerosis only in women

Abstract: Our data suggest that higher circulating levels of 25(OH)D are associated with a lower incidence of MS and MS-related disability in women. This may imply clues to the pathogenesis of the sex difference in risk and to the nature of the environmental factors involved in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
3
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 47 publications
5
107
3
9
Order By: Relevance
“…After MS onset, serum 25(OH)D 3 concentration declines [91] , and hypovitaminosis D is observed throughout the course of the disease, even in a clinically isolated syndrome (CIS) [92][93][94] . Thus, the studies measuring 25(OH)D 3 concentration in patients with MS are uninformative in deciding whether vitamin D can decrease the risk of MS [95,96] . In this case, longitudinal studies based on 25(OH)D 3 concentration before the onset of MS are needed [95] .…”
Section: Vitamin D and Msmentioning
confidence: 99%
“…After MS onset, serum 25(OH)D 3 concentration declines [91] , and hypovitaminosis D is observed throughout the course of the disease, even in a clinically isolated syndrome (CIS) [92][93][94] . Thus, the studies measuring 25(OH)D 3 concentration in patients with MS are uninformative in deciding whether vitamin D can decrease the risk of MS [95,96] . In this case, longitudinal studies based on 25(OH)D 3 concentration before the onset of MS are needed [95] .…”
Section: Vitamin D and Msmentioning
confidence: 99%
“…The 25-OH-D serum level has also been inversely associated with the degree of disability in patients in various stages of MS [Van der Mei et al 2007a;Kragt et al 2009;Smolders et al 2008b]. However, reverse causality (see above) cannot be ruled out for this clinical variable, which concerns patients with a more advanced disease and a permanent disability, consequently variably limiting their outdoor activities.…”
Section: Other Variablesmentioning
confidence: 99%
“…In patients with MS living in temperate and Nordic countries, as in the general populations of these countries, vitamin D insufficiency is widespread, whatever the cutoff (50 or 75 nmol/ liter) for the lower limit of the 25-OH-D serum level ( Figure 3): indeed, as early as the earliest stages of the disease, that is, in patients with clinically isolated syndrome (CIS) or with RRMS, average serum levels are between 42 and 74 nmol/ liter, depending on the studies and the seasons, with a general mean close to 60 nmol/liter [SoiluHänninen et al 2005[SoiluHänninen et al , 2012Smolders et al 2008b;Hiremath et al 2009;Kragt et al 2009;Mowry et al 2010;Pierrot-Deseilligny andSouberbielle, 2010, 2012;Simpson et al 2010;Banwell et al 2011;Dabbaghmanesh and Yousefipour, 2011;Lonergan et al 2011;Neau et al 2011;Steffensen et al 2011;Yildiz et al 2011; Bäärnhielm Kampman et al 2012;Kirbas et al 2012;Løken-Amsrud et al 2012;Moen et al 2012;Runia et al 2012;SoiluHänninen et al 2012;Šaltyte . Benth et al 2012;Triantafyllou et al 2012] (Table 1).…”
Section: Vitamin D Requirements and Insufficiencymentioning
confidence: 99%
“…In women for each 10 nmol/L increase of serum 1,25(OH)2D level was associated with a 20% reduction in the likelihood of MS development suggesting a "protective" effect of higher 1,25(OH)2D serum levels. 40 Correlation between sunlight exposure and MS is confirmed by several evidences such as higher childhood sunlight exposure associated with lower MS risk 66 , lower incidence of non-melanoma skin cancer in MS 67 , inverse correlation between MS prevalence and sunlight and inverse correlation between altitude as a marker of sunlight intensity and MS, so that higher sun exposure during childhood and early adolescence is associated with a reduced risk of MS. 68 The geographical distribution of MS with low prevalence in equatorial regions and increasing prevalence with increasing latitudes in both hemispheres correlates with sun exposure/ vitamin D levels. MS is more common in areas further away from the equator where there is less sunshine, which show a relationship between vitamin D and the risk of developing MS. 69,70 Migrating populations seem to acquire the MS risk of the areas they move to but individuals keep risk of country of origin if move after adolescence 71,72 , that confirm hypotheses of a long latent period in MS development.…”
Section: Vitamin D and Risk Of Msmentioning
confidence: 58%
“…38 Vitamin D is an in vitro potent immune modulator, that can ameliorate, or even cure, animal models with MS. 28 In the other word, a poor vitamin D status could increase risk for MS 39,40 and lead to a more severe disease course of MS. 41 Several experimental studies, have shown that vitamin D brings the immune system in a less pro-inflammatory state. 28 This important role of vitamin D in preventing immune deviation has been argued to underlie the association of a poor vitamin D status with MS.…”
Section: Vitamin D and Auto-immune Diseasementioning
confidence: 99%